Impact of open-irrigated radiofrequency catheter with contact force measurement on the efficacy and safety of atrial fibrillation ablation: a single-center direct comparison - Schlögl, Simon; Schlögl, Klaudia Stella; Bengel, Philipp; Bergau, Leonard; Haarmann, Helge; Rasenack, Eva; Hasenfuss, Gerd; Zabel, Markus (Journal of Interventional Cardiac Electrophysiology, 2022)
In atrial fibrillation (AF) patients, catheter ablation of pulmonary veins (PVI) is the most effective therapeutic option to maintain sinus rhythm. To improve successful PVI, contact force–sensing (CF) catheters became routinely available. Previous studies did not clearly show superior clinical efficacy in comparison with non-CF catheters.